WRITTEN CORRECTIVE FEEDBACK - Pariyanto Pariyanto; Dona Rahayu Sugiharti (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2022)
This paper reports on an exploratory study that investigated learners’ perceptions and preferences of written corrective feedback (WCF) in Indonesian EFL setting. Quantitative and qualitative data were collected from 32 adult English learners studying academic writing. Employing written questionnaire, the study explored the learners’ perceptions and preferences of WCF. The results indicated that the participants (1) mainly expressed a favorable attitude towards error correction or WCF; (2) preferred to revise errors on punctuation (40%), vocabulary (30%), spelling (15%), grammar (10%), and organization (5%); (3) considered commenting on content, grammar, organization, overall quality of writing equally important; (4) believed that WCF is effective when it is presented by underlining the error and then pointing to the correct source of information, showing the location of the error and indicating the type of error, underlining the error, and then telling the correct form, providing corrections for errors and then providing an explanation regarding the improvements; and (5) shared similar opinions about WCF, regardless of their proficiency level. Overall, the findings confirm the significance of WCF for Indonesian EFL learners learning to write.